2021
DOI: 10.3389/fbioe.2021.622099
|View full text |Cite
|
Sign up to set email alerts
|

Improved Posterolateral Lumbar Spinal Fusion Using a Biomimetic, Nanocomposite Scaffold Augmented by Autologous Platelet-Rich Plasma

Abstract: Remodeling of the human bony skeleton is constantly occurring with up to 10% annual bone volume turnover from osteoclastic and osteoblastic activity. A shift toward resorption can result in osteoporosis and pathologic fractures, while a shift toward deposition is required after traumatic, or surgical injury. Spinal fusion represents one such state, requiring a substantial regenerative response to immobilize adjacent vertebrae through bony union. Autologous bone grafts were used extensively prior to the advent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 78 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…In vivo , the composite group produced more trabecular and cortical bone than did the stent group alone, and the fusion rate was better than that of the control group. Quantitative analysis of the expression of key osteogenic genes showed that RUNX2, SPARC, and SPP1 were significantly up-regulated compared to the control group ( Figures 5B–D ) ( 96 ). This appears to be the key to the promotion of bone fusion.…”
Section: Application Of Prp In Spine Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo , the composite group produced more trabecular and cortical bone than did the stent group alone, and the fusion rate was better than that of the control group. Quantitative analysis of the expression of key osteogenic genes showed that RUNX2, SPARC, and SPP1 were significantly up-regulated compared to the control group ( Figures 5B–D ) ( 96 ). This appears to be the key to the promotion of bone fusion.…”
Section: Application Of Prp In Spine Surgerymentioning
confidence: 99%
“…(E) CT evaluation of spinal fusion in different groups. Reproduced with permission from ( 96 98 ). **P = 0.0034, ***p = 0.0002, ****p < 0.0001. e1: Control group.…”
Section: Application Of Prp In Spine Surgerymentioning
confidence: 99%
“…Indeed, the bone density, amount of novel bone and expression of bone-related genes were significantly higher in group 2 when compared to group 1. [198] Gelatin sponge-GS (MHC-3, Kuaikang, Guangzhou, China)…”
Section: Biomaterialsmentioning
confidence: 99%
“…Coating is an effective way to regulate degradation rate of Mg fusion cages (9). Some studies have suggested that fluoride-coated Mg alloy could improve corrosion resistance and promote osteogenic differentiation (10,11).…”
Section: Original Articlementioning
confidence: 99%
“…The F-HP-Mg cages (mainly composed of MgO and MgF 2 ) were made through immersion of HP-Mg cages in a hydrofluoric acid solution (9). Untreated HP-Mg cages of the same size were used as controls in goat models.…”
Section: Sample and Materialsmentioning
confidence: 99%